SURVEI INDEKS MASSA TUBUH TERHADAP TINGKAT KEBUGARAN JASMANI MAHASISWA PGSD UNIVERSITAS MULAWARMAN - Gyta Krisdiana Cahyaningrum; Naheria Naheria; Didik Cahyono; Muhammad Sukron Fauzi; Septyaningrum Putri Purwoto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study aims to determine the body mass index on the level of physical fitness of PGSD students at Mulawarman University. This research is a qualitative descriptive study using anthropometric tests and physical fitness tests. The sample of this study was PGSD students class of 2022 totaling 160 people, who were taken by cluster sampling technique. The results of the research data analysis show that 3.7% of students have a very low BMI, 21.9% of students have a thin BMI, 54.4% of students have a normal BMI, 18.1% of students have a fat BMI, and 1.9% of students have an obese BMI. Next, the level of physical fitness obtained by PGSD students was 3.1% in the very good classification, 11.9% in the good classification, 25% in the moderate classification, 51.9% in the less classification, 7.5% in the very less classification. So it can be concluded that overall the average body mass index on the level of physical fitness of PGSD students class of 2022 Mulawarman University is in the low category.